2021
DOI: 10.1021/acsnano.1c06022
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Tumor Inflammation and Tumor-Platelet Crosstalk by Nanoparticle-Mediated Drug Delivery Mitigates Cancer Metastasis

Abstract: Sowing malignant cells (the “seeds” of metastasis) to engraft secondary sites requires a conducive premetastatic niche (PMN, the “soil” of metastasis). Inflammation and tumor associated platelet (TAP) has been hijacked by primary tumors to induce PMN “soil” in distant organs, as well as facilitate the dissemination of “seeds”. This study reports a combinatory strategy with activated platelet-targeting nanoparticles to aim at the dynamic process of entire cancer metastasis, which exerts robust antimetastasis ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 87 publications
(128 reference statements)
0
17
0
Order By: Relevance
“…Moreover, mouse models have demonstrated that interactions of platelets with numerous cancer cell types (e.g. mammary, colorectal, ovarian, breast) are crucial for cancer metastasis 22 , 59 , 60 . A natural corollary is to evaluate whether the presence of CD55 and/or ADGRE5 neutralizing antibodies abrogates PCa cell-platelet crosstalk and reverses metastatic potential in a nude mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mouse models have demonstrated that interactions of platelets with numerous cancer cell types (e.g. mammary, colorectal, ovarian, breast) are crucial for cancer metastasis 22 , 59 , 60 . A natural corollary is to evaluate whether the presence of CD55 and/or ADGRE5 neutralizing antibodies abrogates PCa cell-platelet crosstalk and reverses metastatic potential in a nude mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue distribution of NPs and diffusion in tumors were examined on H22 tumor-bearing mice after intravenous treatment with mSZ@PDA-NO/US, mSZ#PDA-NO/US, mSZ@PDA-NO/NIR, mSZ@PDA/US, and mSZ@PDA-NO. 65 All animal experiments were performed following the Institutional Guide for the Care and Use of Laboratory Animals of China and the protocols were approved by the Animal Care and Use Committee of Southwest Jiaotong University. Briefly, Kunming mice (∼20 g) were received from Sichuan Dashuo Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…The capture of platelets by P‐selectin was also explored. For example, nanoparticles coated with a P‐selectin‐targeting peptide (PSN peptide) were constructed, and the core of these nanoparticles was filled with ticagrelor or celecoxib 200 . Through capturing activated platelets, these PSN peptide‐modified nanocarriers have improved capability in accumulating at the primary tumor and premetastatic sites, hence robustly inhibiting platelet−tumor interaction and inflammation 200 .…”
Section: Platelets and Cancer Treatmentmentioning
confidence: 99%